Legal Frameworks and Advocacy in Bankruptcy Restructuring: A Comparative Analysis of Financial Service Authorities in Indonesia and the United States - Kurniawan, Itok Dwi; Suwadi , Pujiyono; Soehartono , Soehartono; Fernades, Acacio (Indonesian Journal of Advocacy and Legal Services, 2025)
Bankruptcy is one of the options available for debtors to resolve financial difficulties when the debtor is unable or is estimated to be unable to pay the obligations owed to the debtor's creditors which are due and billed. Everyone seeking justice must follow certain procedures, including bankruptcy and suspension of debt repayment obligations. The application for bankruptcy and suspension of debt payment obligations is the first step, followed by a decision to declare bankruptcy and suspension of debt payment obligations, as well as all legal remedies. OJK has issued a Credit Restructuring Policy based on Financial Services Authority Regulation Number 11/POJK.03/2020 concerning Economic Stimulus as a Countercyclical Policy for the Impact of the 2019 Coronavirus. This procedure will require debtor restructuring to avoid bankruptcy, either through debt restructuring or corporate restructuring. The purpose of this study is to obtain an overview of the implementation of restructuring in the process of bankruptcy and payment delays, as well as a reference for maximizing debtor restructuring plans. This study finds that debt restructuring and deferred payments are mostly debt restructuring and begin with a settlement plan. Rescheduling consists of selling assets, acquiring new equity, and engaging in debt-to-equity swaps. When the debtor arranges a plan restructuring, fixation begins. Some of the main causes are debtors' misunderstandings about how to use the restructuring plan. Furthermore, in other situations, the implementation of the restructuring may fail due to the debtor's inability to manage the business and its obligations.